Computer Anxiety dan Computer Attitude terhadap Kemampuan Mahasiswa Akuntansi dalam Mengoperasikan Software Akuntansi Pada Program Studi Akuntansi Fakultas Ekonomi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
This study proves empirically the effect of computer anxiety and computer attitudes on theability of accounting students to operate accounting software at the Accounting Study Program, Faculty of Economics, Majalengka University.The research method used in this research is descriptive verification method. The populationis all students in the 2017/2018 academic year. The sample is 101 people who have followed financial accounting computer courses. Sampling was using purposive sampling method. Thedata survey method uses a questionnaire media. The test instrument was carried out by testingthe validity and reliability test, while the data analysis was belonging, determination and hypothesis testing.The results showed that partially the variables of computer anxiety and computer attitudeshad a significant effect. Simultaneously, the variables of computer anxiety and computer attitudes have a positive relationship and have a significant effect on the ability of accounting students to operate accounting software.